Segment V spontaneous hepatic haemorrhage from hepatic cirrhosis: an emergency abdominal surgery case report - Bagus, Budhi Ida; Bagus, Metria Ida; Andi, Fittrani (International Surgery Journal, 2019)
A spontaneous hepatic haemorrhage (SHH) is a rare condition that results from a breach in the hepatic parenchyma that occurs without an external cause. It is an acute surgical emergency as it results in intra-abdominal bleeding that, if untreated, will progress to haemorrhagic shock and death. The clinical presentation is often non-specific but emergent, and rapid diagnosis and treatment is required, often involving a number of services including interventional radiology, hepatology and surgery. SHH is a rare event most commonly caused by HCC and hepatic adenoma although there are numerous other causative lesions including all recognized benign and malignant hepatic tumours including metastatic cancer. The mechanism of spontaneous bleeding remains unclear but there is evidence for compromised vascular integrity at least in patients with HCC and the incidence of the condition in patients with connective tissue diseases. A diagnosis of SHH is based on a clinical index of suspicion in patients with a known underlying condition. However, this is not always as straightforward as SHH is a rare complication in patients with connective tissue disease. Spontaneous hepatic haemorrhage is one of acute abdominal emergency case with high morbidity and mortality rate. Emergency operation plays an important role in managing this case.